Predementia states and dementia in young people - A.A. Smirnov; A.V. Gustov; S.V. Kopishinskaya; V.A. Antonova (Неврология, нейропсихиатрия, психосоматика, 2014)
Dementias are much more rarely encountered in young than in older people. However, the highest percentage of dementias is reversible in young patients. The diagnosis of cognitive impairments in this patient category makes it possible to identify the underlying disease and to perform adequate therapy at their early stage. The clinical features of dementias that are most common at a young age and the possibilities of their early diagnosis are covered. The authors describe their own clinical observations in patients with neuroAIDS, Huntington’s disease, or multiple sclerosis.